(3TQM CMhGd HYV GdUMGHI hHYV GdSda GdUGdMjfs - (3YR GdOjf YHO GdYRjR Hf YHO GdSdGe Hf CHh GdbGSe Hf GdMSf GdSdej GdOeTbj GdTGaYj, GHf YHO GdSdGe,J (B660 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdcGed GdaGVd YR GdOjf Hf YHO GdSdGe GdebOSi (B: (3GdMeO ddg GdPi ChOY bdhH ChdjGFg ef dWja Mceg CSQGQkG s
(3BNQgG (B:s
(3aEfc JeMheG JTGA hJKHJ hYfOc Ce GdcJGH s
(3HChdgG agQS ddeJQLejf cJHg GdeZahQ dg CMeO HGTG JjehQs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B21s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B247 s
Keywords: (3GdJGQjNs